Results of shortened program of Ponseti technique for congenital clubfoot - Sugandhavesa N. (Medical Association of Thailand, 2015)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To study the results and complications of congenital clubfoot treatment using a shortened (twice a week) program of serial casting using Ponseti technique. Material and Method: Sixteen patients with congenital clubfoot (26 feet) were treated by serial manipulation and casting twice a week until acceptable deformity correction (60 degrees of abduction with or without equinus deformity) were achieved. Results: Seventeen patients (65%) required less than three weeks in treatment to improvement in the deformity, while eight patients (30%) required more than three weeks of treatment. This period of treatment is at least two weeks shorter than the conventional Ponseti technique. One patient did not complete treatment due to hospital-acquired pneumonia. Four patients who developed pressure ulcers from the castings were continued in treatment and all achieved successful correction. Conclusion: A shortened program of clubfoot correction using the Ponseti technique can be effective for correcting uncomplicated clubfoot without serious complications.